Pendampingan Pemanfaatan Platform Merdeka Mengajar dalam Penguatan Sekolah Penggerak Melalui Optimalisasi Peran Komunitas Belajar - Miftah, Miftah; Napitupulu, Nurasyah Dewi; Zaky, Muhammad (Indonesian Journal of Society Engagement, 2024)
In an effort to improve the quality of education, especially in driving schools, the role of learning communities and the use of technology such as the Merdeka Mengajar Platform is very important to have a positive impact. The purpose of this service is to assist and optimize the role of the learning community in strengthening the driving school through the use of the Merdeka Mengajar Platform with the stages of implementation, namely identifying the needs of driving schools and related learning communities, providing training to understand and optimize the use of the Merdeka Mengajar Platform, forming and strengthening learning communities at the school level through learning community workshops, and monitoring and evaluating program implementation. From this service activity, it is expected that the results and benefits will be in the form of increased utilization of the Merdeka Mengajar Platform by teachers, a more active role of the learning community in supporting learning activities, and strengthening the capacity of driving schools through collaboration with learning communities.